2004
DOI: 10.1007/bf03260057
|View full text |Cite
|
Sign up to set email alerts
|

Catalase enzyme mutations and their association with diseases

Abstract: Enzyme catalase seems to be the main regulator of hydrogen peroxide metabolism. Hydrogen peroxide at high concentrations is a toxic agent, while at low concentrations it appears to modulate some physiological processes such as signaling in cell proliferation, apoptosis, carbohydrate metabolism, and platelet activation. Benign catalase gene mutations of 5' noncoding region (15) and intron 1 (4) have no effect on catalase activity and are not associated with disease. Catalase gene mutations have been detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(129 citation statements)
references
References 84 publications
0
117
1
5
Order By: Relevance
“…The CAT-21A/T polymorphism has not been associated with any alteration in catalase activity [51,79], but individuals carrying the variant T allele presented non-significant higher HDL and lower LDL levels, both before and after pequi-oil supplementation, indicating that this variant allele could be more protective. Although there were differences in the genotype frequencies between the sexes, for clinical purposes, the reference values of lipid profile are equal for men and women [46,67,137], not affecting the results.…”
Section: Discussionmentioning
confidence: 91%
“…The CAT-21A/T polymorphism has not been associated with any alteration in catalase activity [51,79], but individuals carrying the variant T allele presented non-significant higher HDL and lower LDL levels, both before and after pequi-oil supplementation, indicating that this variant allele could be more protective. Although there were differences in the genotype frequencies between the sexes, for clinical purposes, the reference values of lipid profile are equal for men and women [46,67,137], not affecting the results.…”
Section: Discussionmentioning
confidence: 91%
“…[52] Although no effects on catalase expression, catalase activity or association with disease/pathological changes have been reported, [53] results indicated that there are differences among CAT genotypes and more investigations are needed, mainly because pequi-oil significantly decreased DNA damage only in athletes carrying the TT genotype, which also presented no tolerance to increased oxidative stress imposed by H 2 O 2 at 0.25mM. Moreover, there was a significant interaction between subject's effects linking CAT and GSTT1, where, in presence of GSTT1 null genotype, extent of DNA damage depended on the presence or absence of the CAT variant allele.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…GPx are present both in the cytosol and in mitochondria [59]. There are at least eight GPx enzymes: GPx1-GPx8 [60,61].…”
Section: Antioxidant Defensesmentioning
confidence: 99%